Algerian water Security and Strategy of its Realization - Frimeche , Malika (Journal of Human Sciences, 2020)
Algeria as a  very huge Mediterranean country  ( with more than 20Million KM 2 ) is characterized by a distinguished geographic and climatic diversity, and  a remarkable disequilibrium  in matter of population distribution and density , as well as a very important water and irrigation  potentiality, found in internal and external basins that are related directly with Mediterranean sea, in addition to a very important quantity of  desert’s groundwater  . However, Algeria  can be considered as a semi or  arid country similar to  lot of southern Mediterranean countries. So to face this water scarcity,and population’s increasing  needs in this field , it is very necessary to elaborate  an efficient water policy.